PENYEBAB RENDAHNYA MINAT BACA SISWA KELAS VIIIA TERHADAP MATA PELAJARAN IPS DI SMP NEGERI 22 DESA SARI MULYA KECAMATAN RIMBO ILIR KABUPATEN TEBO PROVINSI JAMBI - Yulaikah, Siti - (Pendidikan Sejarah, 2014)
Background of the research is lower interested student for reading historical subject in SMPN 22 Sari Mulya subdistrict Rimbo Illir Tebo province Jambi. Interested for reading is for undrstanding word to word and content of the meaning in context,so reader can understand what they read,in fact based of the research most of students SMPN 22 Sari Mulya subdistrict Rimbo Illir Tebo province Jambi very low to visit library and read seriously in their home. Function of research for know various reason low is interested reading students of class VIIIA toward In social studies learning in SMPN 22 Sari Mulya subdistrict Rimbo Illir Tebo province Jambi. Kind of research is ekspasfacto uses a quantitative approach to research site in SMPN 22 Sari Mulya subdistrict Rimbo Illir Tebo province Jambi. The informan are teacher, the student. Data collection techniques are observation, interviews, documentation. These data were processed using triangulation is checking the validity of the data. Based of the research can be seen that various reason low is interested reading students of class VIIIA toward In social studies learning are internal and external factor.internal f actor is motivate from theirself, interested reading can growing with mental of developing,interest to read fluence from preparing students for study and emotiona,external factor can get neighborhood, family and school. Based of the result research can conclude that various reason low is interested reading students of class VIIIA toward In social studies learning in SMPN 22 Sari Mulya subdistrict Rimbo Illir Tebo province Jambi because the students think material socia subject more difficult for understand and causes by two factors are (1) internal factor and (2)external factor.